Jelena Jovanović, Tijana Kovčić, Vladimir Mijatović, Jelena Nikolić, Logor Sajmište. Žrtve Jevrejskog logora Zemun (Beograd: Istorijski arhiv Beograda, 2018), 467 str. (ćirilica) (Časopis za suvremenu povijest, 2020)
Prikaz knjige